Survival of bifidobacteria in adult intestinal tract - Grmanová, M; Vlková, E; Rada, V; Homutová, I (Folia microbiologica, 2010)
The "cocktail" of human origin rifampicin-resistant bifidobacteria (RRBs) and RRBs from commercial products was administrated to 9 volunteers aged from 22 to 46 years and the survival ability in gastrointestinal tract of these strains was determined. Bifidobacteria represented 0-8 % of total anaerobes detected in gastrointestinal tract of volunteers before the administration of probiotic strains. After the administration of probiotics, bifidobacterial counts increased to 16 % of total bacterial counts. RRBs formed 9-44 % of total counts of bifidobacteria. Then, the counts of RRBs decreased at day 7 after administration, and they were not detected after 14 d. In our study, suitable probiotic bifidobacterial strains for human should be chosen on the basic of in vitro test but the results showed that no strain was able to colonize human tract permanently.
Keywords: probiotika; Adult; dospělí; Probiotics; Human Experimentation; Humans; Bifidobacterium; lidé; experimenty na lidech; lidé středního věku; Gastrointestinal Tract; Colony Count, Microbial; mikrobiální viabilita; gastrointestinální trakt; Microbial Viability; Middle Aged; počet mikrobiálních kolonií